2010
DOI: 10.1111/j.1524-475x.2010.00578.x
|View full text |Cite
|
Sign up to set email alerts
|

New dressing materials derived from transgenic flax products to treat long-standing venous ulcers-a pilot study

Abstract: A new flax dressing product was developed based on three components (fibers, oil emulsion, and seedcake extract) from genetically engineered flax plants that were obtained by plant transformation using three genes controlling the synthesis of antioxidative compounds from the phenylpropanoid pathway. Simultaneous flax explant transformation with three genes coding for chalcone synthase, chalcone isomerase, and dihydroflavonol reductase resulted in an accumulation of phenolic acids in the fibers, polyunsaturated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 35 publications
1
42
0
1
Order By: Relevance
“…The presence of cannabidiol in flax is interesting not only in the aspect of its so far unique natural source (Cannabis plants) but primarily for its natural synthesis in fibers which when used for wound dressing production might offer antiinflammatory and anti-analgesic activity. Recently, the treatment of patients suffering from chronic wounds of different aetiology with flax wound dressing resulted in inflammation reduction [7]. The results of the clinical study are perhaps now clearer; the presence of CBD within fiber compounds might be at least partially responsible for this positive effect.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…The presence of cannabidiol in flax is interesting not only in the aspect of its so far unique natural source (Cannabis plants) but primarily for its natural synthesis in fibers which when used for wound dressing production might offer antiinflammatory and anti-analgesic activity. Recently, the treatment of patients suffering from chronic wounds of different aetiology with flax wound dressing resulted in inflammation reduction [7]. The results of the clinical study are perhaps now clearer; the presence of CBD within fiber compounds might be at least partially responsible for this positive effect.…”
Section: Discussionmentioning
confidence: 66%
“…It has been widely proven that high levels of ALA can reduce the risks of cancer and cardiovascular diseases and decrease the production of arachidonic acids and other eicosanoids, which are known inflammation mediators [5,6]. The results of our latest investigations suggest that not only can the flax seeds and the oil be used in medicine, but also the fibers appear to be a valuable material for wound dressing [7]. Analysis of previously generated transgenic plants, overexpressing genes from the flavonoid synthesis pathway, showed increased levels of many phenylpropanoids, resulting in higher antioxidant capacity, fungal resistance, oil stability and SDG content increase [8].…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…As the polyphenol extracts of seed cakes of hemp (Cannabis sativa), flax (Linum usitatissimum) and canola (Brassica napus) have not been studied in detail yet, information on single effective compounds would be of interest, since the polyphenols that exhibit functional and nutraceutical properties could also be used in functional food, additionally to its use in feed. Previous studies showed the improvement of human health by antioxidant compounds, such as healing human chronic ulceration, inhibition of cancer cells, improving the condition of cardiovascular diseases and diabetes, anti-inflammatory, anti-microbial, antiviral, anti-allergenic, anti-artherogenic, antioxidant, anti-thrombotic, cardioprotective and vasodilatory effects [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the cytotoxicity of flax fibres, oil emulsion, and seedcake extract from transgenic flax overproducing various antioxidative compounds was determined in a culture of mouse fibroblasts. No changes in the total number of fibroblasts and comparable numbers of dead cells were shown in the presence of each type of flax material (Skorkowska-Telichowska et al 2010). In order to improve the biochemical and mechanical properties of flax fibres, transgenic flax over-expressing the bacterial polyhydroxybutyrate (PHB) gene was produced (Wrobel et al 2004;Wrobel-Kwiatkowska et al 2007).…”
Section: Biocomposites Containing Flax Fibers In a Polyester Matrixmentioning
confidence: 99%